Retrospective analysis of results of treatment for nasopharyngeal carcinoma in Macao - Dou, Huiqin; Hu, Dongyan; Lam, Chileong; Liu, Yunsheng; Wang, Xiuwen; Zhang, Wendong (Chinese Journal of Cancer Research; Vol 26, No 2 (April 26, 2014): Chinese Journal of Cancer Research, 2014)
Background: Nasopharyngeal carcinoma (NPC) is a common malignancy in Southeast Asia, however, a full consensus has not yet been reached as to the value of comprehensive treatment for NPC. This study was designed to evaluate the epidemiological characteristics of NPC and their prognostic value, as well as the long-term efficacy of NPC treatment. Patients and methods: A total of 248 patients, with different stages of NPC, were included in this study. Results: The 5-year overall survival (OS) rates for patients in stages I, II, III and IV were 90.48%, 76.71%, 76.89% and 33.87%, respectively (P=0.000), while the respective 5-year progression-free survival (PFS) rates were 85.15%, 72.36%, 63.88% and 26.26% (P=0.000). The respective 5-year OS rates, according to stage, for the group that received radiotherapy combined with chemotherapy and for the group that received radiotherapy only were as follows: stages I and II, 81.67% and 79.59% (P=0.753); stage III, 79.91% and 70.38% (P=0.143); stage IV, 35.22% and 0% (P=0.000). The respective 5-year PFS rates in these groups were as follows: stages I and II, 75.83% and 74.98% (P=0.814); stage III, 74.08% and 42.25% (P=0.027); stage IV, 27.31% and 0% (P=0.000). Conclusions: Clinical staging appears to be the most important prognostic factor for NPC. As the stage number increases, both the 5-year OS and PFS significantly decrease. Adding chemotherapy to radiotherapy was not advantageous for patients with stage I or II NPC, however the addition of chemotherapy to radiotherapy significantly improved OS and PFS in patients with stage IV NPC. The addition of chemotherapy improved PFS, but not OS in patients with stage III NPC.